Effect of Adoption Intensity of Climate Smart Agriculture on Farming Households’ Food Security in Ethiopia: Empirical Evidence From Guna Begemider District, South Gonder - Mekdes Teklemichael; Abate Mekuriaw (SAGE Open)
This paper assessed the adoption intensity of CSA practices and their effect on food security among farming households in Guna Begemider district, South Gonder Zone, Ethiopia. A semi-structured questionnaire was administered among 217 randomly selected households from four kebeles of the district. Food security was measured in two ways; per capita calories (as a continuous variable) and the daily minimum dietary energy requirement for an average adult to function actively (dummy variable with a cut point at 2,100 kcal). Descriptive analysis, multiple linear regression and binary logistic regression were employed to analyse the data. The study found that the great majority of the households adopted CSA practices and the average adoption intensity was 7 out of the 19 practices. The average daily per capita dietary energy was 2,130.21 kcal with a minimum of 352.18 kcal and a maximum of 7,456.03 kcal. However, about 59.45% of the households live below the minimum daily calorie requirements (2,100 kcal). Adoption intensity of CSA practices and agricultural experience were found to have a positive effect on food security both in measurements of per capita calories and daily minimum dietary energy requirement. On the contrary, household size and kebele of residence showed a significant but negative effect on food security in both measurements. The study concludes that adopting a layer of CSA practices can make a crucial contribution to address the potential impact of climate change on agriculture and food security.